"That type of thing does give you a boost": Control, Self‐valorisation, and Autonomist Worker Copings in Call Centres. Issue 5 (20th September 2019) - Hastings, Thomas; Cumbers, Andrew
Abstract: There are growing concerns over current and future incarnations of routine work, based on the rise of technology and its perceived impact on skill requirements in the labour market. Drawing on Autonomist Marxist (AM) literature, the following article demonstrates how and why workers are likely to play a role in maintaining meaningful forms of work. Complimenting labour process research, which focuses on the role of worker "resistance" in the workplace, we develop a more nuanced perspective on worker agency and the human potential to create meaning through self‐governance in even the most unlikely service work encounters. Taking resilience and reworking agencies as subtle forms of "self‐valorisation", we show how different spaces of routine work are mobilised for reproducing human connections and values in ways which act in opposition to management's control and the evolution of unpleasant work environments. Riassunto: La natura, presente e futura, del lavoro routinario costituisce una crescente preoccupazione, dato l'aumentato utilizzo della tecnologia e date le competenze specifiche ora richieste dal mercato del lavoro. Il presente articolo si basa sulla letteratura sull'autonomia operaia e dimostra come e perché i lavoratori possano influenzare la continuata esistenza di forme di lavoro importanti. Contribuendo alla ricerca sul processo del lavoro, la quale si focalizza sulla "resistenza" del lavoratore nel contesto lavorativo, sviluppiamo una prospettiva più approfondita sul ruolo del lavoratore e del potenziale umano nella creazione di scelte importanti e autonome sulle attività lavorative da intraprendere. Considerando la resilienza e la rielaborazione dei lavoratori come forma di "auto‐valorizzazione", mostriamo come in diversi ambienti di lavoro routinario vengano sviluppati nuovi valori e nuove relazioni umane che agiscono in opposizione al controllo manageriale e all'evoluzione di ambienti lavorativi sgradevoli.